Análisis de los elementos constitutivos de la turbina Michel Banki aplicada a estaciones de bombeo cuyo fin es identificar las zonas influyentes en el rendimiento del sistema. - Rivera Balcázar, Juan Carlos (2013)
The purpose of this work is the fundamental parameters approach the design and construction of a model for the hydraulic laboratory Michell Banki turbine and testing to evaluate its performance characteristics. The Michell Banki turbine is a turbomachine of action, cross flow, partial admission and dual effect. The hydraulic design is based on data provided by the recirculation hydraulic pump installed in the laboratory, with a fall of 1.5 meters head and a flow rate of 24 lt / sec, it raises the design equations, after a review of alternatives which determines the basic geometry of the turbine, for which it is considered an important factor in ease of construction materials available on the market. Based on the selected model and forces are calculated due to the jet torque on the blades and main shaft, and then proceed to its mechanical design. Build the model is determined by testing the real power and efficiency at which the machine operates. In the course of the tests and the results obtained are set total yield Michell Banki turbine.